Antiviral activity and mode of action of propolis extracts and selected compounds - Schnitzler, Paul; Neuner, Annett; Nolkemper, Silke Anneli; Zundel, Christine; Nowack, Hans; Sensch, Karl Heinz; Reichling, Jürgen (Phytotherapy research, 2010)
Aqueous and ethanol extracts of propolis were analysed phytochemically and examined for their antiviral activity in vitro.